Santripreneurship in Practice: A Model of Entrepreneurship Development at Sunan Drajat Islamic Boarding School, Lamongan - Falach, Alifya Nurul; Ridwan, Muhtadi; Zenrif, Muchammad Fauzan (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2023)
The growing role of Islamic boarding schools (pesantren) in community-based economic development highlights the need for models that integrate entrepreneurship with spiritual values. This study aims to develop a santripreneur model at Sunan Drajat Islamic Boarding School (Pesantren), Lamongan. Using a qualitative case study design, data were collected through in-depth interviews, focus group discussions, direct observation, and document analysis across the pesantren’s business units. The findings identify a structured four-stage trajectory—startup, stabilization, growth and development, and real business synergy—that reflects the transformation of santri into Islamic entrepreneurs. This model integrates Islamic spiritual values with modern business practices, emphasizing tawḥīd, ethical conduct, performance discipline, and stakeholder collaboration. It not only cultivates an entrepreneurial mindset rooted in Shariah principles but also promotes institutional sustainability through structured training and alumni engagement. Conceptually, the model addresses a gap in the Islamic entrepreneurship literature. Practically, it offers a replicable framework for other pesantren seeking a sustainable, Shariah-compliant economic ecosystem.